Implication Extradisi, Mutual Legal Assistance (UNODC) Dikaitkan Teori Pidana, Perjanjian Internasional - Rahmiati Rahmiati; Rahmad Sujud Hidayat; Mohamad Safrin; Juandi Juandi (Wajah Hukum, 2023)
Extradition agreements based on the international resolution A/RES/45/166 68th Plenary meeting on 14 December 1990 in conjunction with A/RES/52/88 70th Plenary meeting on December 12, 1997 for making extradition treaties and mutual legal assistance internationally.This  propose the problem identification as follows: 1. What are the important articles suggested in the extradition treaty and mutual legal assistance related to criminal theory and international treaties. 2. How is the application and implementation of the extradition and mutual legal assistance based on the national and regional especially In Indonesia.This research conducted is analytical descriptive. Here is the research results, as follows: 1.) Important articles suggested in the extradition treaty are the principle of nebis in idem, the principle of multiple crimes and the diplomatic principle and the mutual legal assistance is the principle of agreement, the principle of reciprocity, the principle of equality of crimes, the principle of territoriality and the principle of surrendering the perpetrators of political crimes. 2) The implementation of extradition treaty model and the mutual legal assistance from the national and regional legal aspects. Based on the regional aspect, Indonesia is the most active country in realizing a cooperation within an agreement.